THE ROLE OF TEACHER ASSOCIATION REGIONAL ON ISLAMIC RELIGIOUS EDUCATION IN SELAYAR ISLANDS - Dudi Hermawan; A. Marjuni; Muh. Rapi (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This paper discusses the Professional Competence of Teachers in Selayar Islands Regency.The purpose of this study was to determine the form of professional competence of PAI (Islamic education) teachers in Selayar Islands Regency. In addition, Islamic education teacher association (AGPAI) contribution in developing the professional competence of PAI teachers in the Selayar Islands Regency. Furthermore, the results of the professional competence development of PAI teachers in the Selayar Islands Regency. This type of research is a descriptive qualitative case study in the Selayar Islands Regency. The results of this study show that the form of professional competence of PAI teachers is seen from various assessments including mastery of materials, structures, concepts, and scientific mindsets that support PAI subjects.